(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
First Colombian Caribbean record of Clypeaster ravenelii and Centrostephanus longispinus rubicingulus (Echinodermata: Echinoidea). This paper reports the first record of Clypeaster ravenelii (Clypeasteridae) on the Southern Caribbean and C e n t rostephanus longispinus rubicingulus (Diadematidae) on Colombian Caribbean coast, based on specimens collected on the continental shelf off the Guajira Peninsula .